Sistem Jaminan Produk Halal Dan Thayib Di Indonesia: Tinjauan Yuridis dan Politis - Murjani, Murjani (FENOMENA, 2015)
The objective of this study was to describe the ideal guarantee system of halal and thayib product from the juridical and politics aspects in the context of Indonesia. The research methodology is normative law research and literature approach. The data consists of primary law data, secondary law data, and tertiary law data. Then, the data were edited, classified, and explained descriptively. The data were analyzed by using inductive methods and content analysis. This study tried to describe the problems of current product guarantee system (ius constitutum) and the upcoming product guarantee system (ius contituendum). The study found that the need of halal product is dharuriah,and obligatory. It have the important benefits to Moslems. The problems of regulation overlapping in Indonesia should be ended by unification of the law, that is, the establishment of the regulation of halal product guarantee where BNP2H becomes the institutional halal product office. Meanwhile, MUI still have a strategic role, since it develops the construction of halal product guarantee system together with BNP2H. MUI is the only institution which has the authority to certify halal or non-halal of a product. This policy becomes a bridge to develop a unification of law and the uniform of institution of the halal product offices, so that, there is no more dualism institutions which certify halal product. It guarantees the system of halal product for Moslems in Indonesia.